Use of Interdisciplinary Links in the Training of Future Specialists in Statistics - Kozlov, V. V.; Tomashevska, T. V.; Kuznіetsov M. I. (Statistics of Ukraine, 2018)
In the article the authors substantiate the importance of establishing and using interdisciplinary connections in the training of future specialists in the field of statistics. This is due to factors such as the transition of the Ukrainian economy to the innovative way of development and the necessity of building state information infrastructure. The training of interdisciplinary specialists, who use statistics, computer science, and data science in their activities, becomes a public need. The authors argue that the modern system of higher education needs to develop innovative teaching approaches in preparing future specialists in the field of statistics, primarily natural-scientific interdisciplinary links. They promote increase of the practical, scientific and theoretical training of students, with their help the foundation for a comprehensive vision, approach and solving complex problems of real reality are laid. In the article special attention is paid to establishing links between computer science and mathematics in the training of future statisticians. The analysis of bachelor programs of various educational institutions has shown that the disciplines of the cycle of mathematical preparation are basic. Computer at various stages of these disciplines can perform functions of control, training, analysis, synthesis, etc. The future specialist should be trained in working with professional mathematical packages that may be needed for him in future professional activities. The authors also note the risk of methodically illiterate implementation of interpersonal links with the use of information technology, when the external ease of use of software tools leaves in the shadows the applied component of the course of higher mathematics. This can lead to a disturbance of dynamic balance and a decrease in the quality of education. The analysis of the problem of interdisciplinary connections shows that it is necessary to transit to updated statistics training programs, oriented to the needs of economic and social development of society. Thus, interdisciplinary links not only allow the establishment of peculiar “bridges” between educational disciplines, but also, on the basis of the common content of these disciplines, to build a holistic system of learning, which is an important condition for an integrated approach that allows to distinguish between the main elements of the content of education and interrelationships between educational subjects.